KONTROLSAMFUND OG KANONBÅDSDIPLOMATI - ET FORSØG PÅ AT ADRESSERE SPØRGSMÅLET OM KOMBINATIONEN AF DECENTRALE NETVÆRK OG SUVERÆNITET EFTER 9/11 MED UDGANGSPUNKT I DELEUZES “POSTSCRIPTUM OM KONTROLSAMFUNDET” - Bolt, Mikkel (K&K - Kultur og Klasse, 2010)
CONTROL SOCIETY AND GUN BOAT DIPLOMACY An attempt to address the question of the relationship between decentred networks and sovereignty after 9/11 starting from Deleuze’s “Postscript on the Societies of Control”. In 1990 Gilles Deleuze published his short text “Postscript on the Societies of Control” in which he presented an almost intuitive analysis of contemporary capitalist society explaining how we were going from the separate spheres of disciplinary society to a flexible network-based society where the traditional discourses and institutions were being broken down in favour of a continual control where the individual was always in school, in prison or at work. Deleuze’s brief text was highly influential but since 9/11 and the declaration of the so-called ‘war on terror’ it has seemed necessary to supplement the analysis of the complex functioning of the control society with analysis that either stress the return of sovereignty (like Giorgio Agamben) or map the workings of capitalist economy (like David Harvey). This paper looks at this development and discusses the relationship between networks and sovereignty today.